ISTIBDAL IMPLEMENTATION: A CASE STUDY OF WAQF LAND ACQUISITION BY THE STATE AUTHORITIES IN KEDAH (International Seminar on Syariah and Law (INSLA), 2022)
This article explores the application of istibdal, a method of managing and preserving waqf (Islamic endowment) lands, particularly in the context of land acquisitions by state authorities in Kedah, Malaysia. It focuses on understanding istibdal from an Islamic perspective and investigating its practical use in the region. This research evaluates several instances of waqf land acquisition by state bodies, seen as permissible for public purposes, and how istibdal serves as a strategic approach to safeguard the continuous benefit of the waqf. Employing a qualitative methodology, data were sourced from an array of Islamic texts, legal documents, fatwas, and academic articles. A case study conducted at Majlis Agama Islam Negeri Kedah (MAIK) provided in-depth, specific insights. The findings underscore the significance of istibdal as an effective tool in managing waqf assets amidst state-level land development, contributing valuable knowledge to the field of Islamic asset management.